Words of a Leader: The Importance of Intersectionality for Understanding Women Leaders’ Use of Dominant Language and How Others Receive It - Dupree, Cydney Hurston (Administrative Science Quarterly, 2024)
Management scholars have long examined gender disparities in leaders’ communication and followers’ reactions. There is, however, a paucity of research that takes an intersectional perspective. This article takes that step, using an intersectional lens to examine women leaders’ use of dominant language and how others receive it. Leveraging advances in natural-language processing, I analyzed the stereotype content of more than 250,000 Congressional remarks (Study 1) and almost one million tweets (Study 2) by leaders. Women leaders referenced dominance more than men did (using more words like “powerful”), violating stereotypes that depict women as submissive. However, as theory on racialized gender stereotypes suggests, this effect was unique to White leaders. Two additional studies revealed backlash to women leaders’ use of dominant language. Analyzing almost 18,000 editorials revealed the more that women leaders referenced dominance, the more they were portrayed as dominant but also cold. Effects were strongest for Black and Latina women (Study 3). Finally, an experiment using simulated social media profiles found the more that Black women (but not men) leaders referenced dominance, the more voters rated them as less likeable, a result that was unique to Black leaders (Study 4). The article demonstrates the critical importance of intersectionality for understanding gender inequality in leaders’ communication and its reception by the media and the public.